1996
DOI: 10.1021/om950953j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of the Reactions of Silicon−Carbon Double Bonds. Addition of Alcohols to 1,1-Diphenylsilene

Abstract: The addition of water, aliphatic alcohols, and acetic acid to 1,1-diphenylsilene (generated by photolysis of 1,1-diphenylsilacyclobutane) has been studied in polar solvents using steadystate and nanosecond laser flash photolysis techniques. Absolute rate constants and (selected) deuterium kinetic isotope effects for the addition of water, methanol, ethanol, 2-propanol, tert-butyl alcohol, and acetic acid have been determined at 23°C in acetonitrile solution. Silene quenching follows a linear dependence on quen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 27 publications
13
75
0
Order By: Relevance
“…Quantum yields for disappearance of 4-6 were determined by 254 nm merry-go-round photolysis of deoxygenated 0.03-0.04 M solutions in hexane containing methanol (0.05 M), using 1,1-diphenylsilacyclobutane (1) as actinometer. Photolysis of 1 in methanolic hexane solution affords ethylene and diphenylmethoxymethylsilane (16) as the only detectable products (2, 4, 11) -the latter due to trapping of 1,1-diphenylsilene (2) -and is characterized by a quantum yield of Φ 2 = 0.21 ± 0.03 (11). Quantum yields were calculated from the relative slopes of plots of concentration vs. photolysis time, which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantum yields for disappearance of 4-6 were determined by 254 nm merry-go-round photolysis of deoxygenated 0.03-0.04 M solutions in hexane containing methanol (0.05 M), using 1,1-diphenylsilacyclobutane (1) as actinometer. Photolysis of 1 in methanolic hexane solution affords ethylene and diphenylmethoxymethylsilane (16) as the only detectable products (2, 4, 11) -the latter due to trapping of 1,1-diphenylsilene (2) -and is characterized by a quantum yield of Φ 2 = 0.21 ± 0.03 (11). Quantum yields were calculated from the relative slopes of plots of concentration vs. photolysis time, which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1,1-Diphenylsilacyclobutane (1) affords 1,1diphenylsilene (2; eq. [1]) with reasonable efficiency (Φ 2 = 0.21), and time-resolved experiments have shown that silene formation occurs on the nanosecond time scale and cannot be quenched by saturation of the solution with oxygen or other triplet quenchers (11). The reactive excited state is thus most likely the lowest excited singlet state, which in these cases is predominantly of benzenoid π,π* character.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The Ph-Si C -conjugation can also be attenuated by twisting the phenyl rings out of the plane of the silene moiety. Increased number of ortho-methyl groups bonded to the phenyl substituents of Ph 2 Si CH 2 (59) weakened the conjugation as indicated by a blueshift in λ max of 30 nm when going from 59 to 61a-61f [101,102].…”
Section: Uv-vis Absorption Spectramentioning
confidence: 99%
“…This behavior is also analogous to what has been observed previously for the addition of oxygen-centered nucleophiles to these two silenes. 15,18,21 In the case of oxygen-centered nucleophiles, we have recently shown that these trends are due, at least to some extent, to the effects of weak complexation of the free silene…”
Section: Discussionmentioning
confidence: 99%